TEPUNG RUMPUT LAUT MENURUNKAN KADAR LDL (LOW DENSITY LIPOPROTEIN) PLASMA TIKUS WISTAR HIPERKOLESTEROLEMIA - Julyasih, K. Sri Marhaeni (UPN VETERAN JAWA TIMUR, 2012)
In Bali there are several types of seaweed that is often consumed as a vegetable, such as Caulerpa spp. (local name Bulung Boni), Gracillaria spp (local name Bulung Sangu) and Euchema spinosum, its potential effect in lowering blood cholesterol levels, therefore it is necessary to determine of plasma low density lipoprotein (LDL) cholesterol level of Wistar rat after treated Caulerpa spp, Gracillaria spp. and Euchema spinosum. This experimental study used completely randomized design Research using using a total of 32 Wistar rats divided into eight sample groups. The eight sample groups were respectively designated as negative control group, positive control group, and six treated sample groups, respectively fed orally with a dose of 1 g and 1,5 g seaweed powder of Caulepa spp. 1g and 1,5 g powder of Gracilaria spp., and 1 g and 1,5 g Euchema spinosum per 100g body weight per day. Each treatment was repeated four times. Our study showed that rat fed with high cholesterol diet and treated Caulerpa spp., Gracilaria spp., and E.spinosum with a dose of 1 g and 1.5 g/100 g body weight rat / day were associated with statistically significantly lowered plasma LDL level (p <0.05) as compared with those of rats fed with high-cholesterol diet without treatment with Caulerpa spp., Gracilaria spp., and E.spinosum.Keywords : Caulerpa spp., Gracilaria spp., E.spinosum, LDL, hyperholesterolemic